“Shadows of the Good Things to Come” CONFESSION AND REPENTANCE: THE INTERFACE BETWEEN CHRISTIANITY AND IGBO INDIGENOUS RELIGION - Odili, Jones Ugochukwu (Asian Horizons, 2013)
There are everyday occurrences that make one to wonder if one can truly be African and truly Christian. In the late 1990’s at Delta State University, Abraka, I had an unforgettable experience, given my pentecostal background, that called for a question of my “level” of conversion. At the Abraka River Resort I heard a European saying “Up, up, Jesus, down, down mummy water! Come in and swim. Mummy water can do you nothing,” while swimming in the river which is generally believed to be a mysterious one. Being conscious of the African concept of the potency of mermaid spirits, being terrified, I hurriedly left the resort for home. At home he wondered the audacity by which the European could say such a thing. Was he not actually born again in the strict sense of it? I concluded that the European might not have had a conscious or a priori knowledge of the existence and potency of mermaids. In 2009, during my doctorate degree programme at the University of Port Harcourt, I had another baffling experience that seems more puzzling than the one just mentioned. I was stung to hear an eminent Roman Catholic priest, scholar and professor in African Traditional Religion say, “On no condition may I eat ewi (rabbit). It is my clan’s totem.” I quickly recalled that I too do not eat snails on the grounds that it is my clan’s totem. However there was an incident that led me to assume that there is an interface between Christianity and indigenous religions of the world.